KAJIAN TRANSFORMASI VISUAL DESAIN KARAKTER BULBASAUR PADA GAME POKEMON GO GENERASI I - Ricky Widyananda Putra (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2016)
Game Pokemon Go is one form of representation of the culture medium which presents a simulated world by building signs in it through the storyline, gameplay, environments, and characters the game, so it becomes a digital culture. Pokemon character design, in this case is Bulbasaur, capable of causing factors curious and addicted to the players as a result of the application of methods manga- matrix, color theory, and techniques of morphological forced connections through visual transformation of character design. This study is a qualitative research based on the application of the principle of manga-matrix includes internal and external factors on the character, the analysis of similarities or relationships between theories related to visual elements and interpretation of the meaning of the characters, as well as a mix of theories on character designs reflecting the ideology of Satoshi Tajiri in terms implementation of Japanese culture. The identification results of data analysis visual transformation of the character designs Bulbasaur has much in common with the presence of additional elements on the diversity of character visualization Bulbasaur. Variety Bulbasaur form the foundation for thinking and the creation of the character as a media introduction of visual transformation of a game character design.